A new approach to design of anti-corrosive three layers self-stratifying coatings. (4th May 2021) - Zahedi, S.; Ghaffarian, S. R.
ABSTRACT: A self-stratifying coating contains at least two resins of different nature, which spontaneously stratify after applying on a substrate. Various self-stratifying systems are reported in the literature, however self-starting coatings, with three layers containing anti-corrosive pigments, and their properties are rarely discussed. In this paper, self-stratifying coatings from epoxy resin and fluorinated ethylene-vinyl ether containing three pigments i.e. zinc dust, micaceous iron oxide, and titanium dioxide have cooperated in formulations. The viscosity of the total mixture has a great effect on stratification and pigment locations. Xylene as a solvent has been used for these formulations. The results show the ratio of binders and different pigment percentages in formulations has not a great effect on the stratification and location of pigments. In addition, the type of solvents with different evaporation rates does not have an effect on stratification and location of pigments in this system.